Modified Fuzzy method for Vertical Handoff in Heterogeneous Networks - Silki Baghla, Harvinder Gill, (International Journal of Scientific Research and Management (IJSRM), 2014)
There are various types of networks in wireless technologies, having different parameters and their specifications and thus having different QoS (Quality of Service). So for moving the MS from one network to another network vertical handoff is required. In this paper we designed the simulation model having seven parameters for vertical handoff between WWAN and cellular network with the help of Fuzzy Logic Tool Box, which is also named as FQDA (Fuzzy Logic Quantitative Decision Algorithm) and Simulink of MATLAB platform. The results show the improved performance and reduced complexity. In this work only 81 rules have been used as compared to 2187 rules needed for 7 attributes.This modified fuzzy method also result in lesser number of handoffs as compared to traditional method.